Human Cutaneous Leishmaniosis in Iran, Up to Date-2019 - Mohamad Reza Razavi (Tehran University of Medical Sciences, 2022)
Cutaneous leishmaniasis is a neglected and parasitic vector borne diseases that is endemic in tropical and subtropical countries, including Iran. The aim of this study was to explain the present status of CL in Iran. This report is based on data that recorded by cutaneous leishmaniasis surveillance system in 2019, and evaluated in Center for Communicable Diseases Management in Ministry of Health in Iran. Iran has been considered an endemic area for cutaneous leishmaniasis in the world. Dependent to activities for cutaneous leishmaniasis control the number of cases decreased from 23202 in 2008 (Incidence rate 32 per 100000) to 13124 in 2019 (Incidence rate 15.8 per 100000), more cases reported from September to December, in 2019, 46% of cases had one lesion and 21% had 2 lesions, 85% of cases diagnosed when the diameter of lesions had 3 centimeters and bellows.